Singular value analyses of voltage stability on power system considering wind generation variability - Pina, Aline Petean [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Transmission Systems worldwide, that were designed and built to operate with predominantly conventional synchronous generation, are advancing to integrate large amounts of renewable energy generators. These renewable generators are sited at resource-rich locations, causing a geographical shift in power injections into transmission systems, subjecting them to undue stress and making them operate in new states. In many transmission systems, capacities to integrate wind resource are exhausted or are being upgraded to accommodate higher wind generation penetration. Examples may be seen in Germany, Ontario (Canada) and Texas. In these situations, where transmission system capacities have been reached, it is important to assess voltage stability by considering (a) wind generation and (b) possible effect of uncertainty in forecast. In this work, a systematic approach of studying voltage stability is proposed. Using an optimal power flow algorithm, the Hessianmatrix of power balance equations is determined that relates changes in minimum singular values of system Jacobian to changes in bus-wise real power injections. This relationship is used to examine effect of uncertainty of wind power forecast on voltage stability. The proposed method is used to study the effects of uncertainty on system voltage stability of 6-bus, 57-bus and 118-bus IEEE and 45-bus South Brazilian test systems, for the real analyses is used 600-bus and results are reported. Considering the simplification of computation, the proposed method has a clear advantage compared to the conventional Jacobian technique using repeated OPF solutions

Os sistemas de transmissão em todo o mundo, que foram projetados e construídos para operar, predominantemente, com geração síncrona convencional, como a geração hídrica. Entretanto, agora se faz necessária a integração de energia renovável, tais como a energia eólica e energia solar. Estes geradores de energias renováveis estão localizados em locais ricos em recursos, causando uma injeções de potência em sistemas de transmissão, submetendo-os a indevidos esforços e obrigando-os a operar em novos pontos de operação. Em muitos sistemas de transmissão, a capacidade de integração se aproximou do limite, sendo necessárias atualizações para acomodar uma maior penetração de geração eólica. Os exemplos podem ser vistas na Alemanha, Ontario (Canadá) e Texas. Nestas situações, onde as capacidades do sistema de transmissão estão próximas do limite de operação, é importante para avaliar a estabilidade de tensão, considerando (a) a geração eólica e (b) possível efeito da incerteza na previsão. Neste trabalho, é proposta uma abordagem sistemática para estabilidade de tensão. Com a utilização de um algoritmo de fluxo de potência ótimo e da construção da matriz hessiana, será determinada a relação entre as mudanças nos valores mínimos singulares do sistema Jacobiano e as mudanças na injeção de potência no barramento em tempo real. Esta relação é usada para examinar o efeito da incerteza da previsão de energia eólica na estabilidade de tensão. O método proposto é usado para estudar os efeitos da incerteza sobre a estabilidade de tensão dos sistemas 6-barras, 57-barras e 118-barras do IEEE; do Sistema Sul Brasileiro reduzido e também foi usado um sistema real 600 barras. Os resultados são detalhados nesta tese
Keywords: Energia - Fontes alternativas; Sistemas de energia eletrica - Estabilidade; Energia eólica; Energia solar; Renewable energy sources